Electron microscopy characterization of the tribolayer formation mechanism in sintered Cu-based composites under dry sliding. (March 2022) - Lee, Hyunjong; Kim, Kyung Il; Kim, Jongbeom; Pin, Min-Wook; Oh, Kyu Hwan; Kim, Kyung Taek
Abstract: In this study, the effect of Cu matrix grain size in sintered Cu-based composites on the microstructural evolution of tribolayers and the resulting tribological properties were investigated. We observed that the hardness of composite and wear dynamics of the Cu composite significantly affected the composition and stability of the tribolayers. As a result, the characters of tribolayers are divided into Fe oxides or Cu with different areal coverages of the surrounding amorphous phase by electron microscopy study. Also, we figured out the self-lubricating property of the tribolayer plays a critical role in deciding the tribological properties such as friction coefficient or wear resistance. Based on analysis, we determined the optimal sintering conditions of the Cu-based composites as 800 °C and 40 MPa for their industrial application; the composite sintered under these conditions possessed an ultrathin and robust tribolayer with high C content.